2021
DOI: 10.1002/crat.202100125
|View full text |Cite
|
Sign up to set email alerts
|

Activating ZnO‐Based Hierarchical Particles for Visible Light Dependent Photocatalytic Performance via Cr‐Incorporated Rapid Chemical Synthesis

Abstract: Flower like nanostructured ZnO hierarchical particles termed as NSPs exhibit high surface area as well as defect free growth which makes them competent for further exploration. In this work, a simple chemical approach to incorporate Chromium (Cr) as dopant in ZnO NSPs is utilized, ensuring the combined effect of effectual nature of pristine ZnO NSPs as well as visible light harvesting character owing to the Cr-doping. Using a simple wet-chemical approach, developed Cr-doped ZnO NSPs are developed having apprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Pristine, element-doped zinc oxide (ZnO), and the construction of heterojunctions with various semiconductors have made ground in many solar-related applications, such as energy conversion and storage, solar water splitting, solar cells, and photocatalytic water treatment. Especially, ZnO nanomaterials maintain their popularity due to their high optical absorption, high resistivity against photocorrosion, easy manipulation of morphology, and electrical and catalytic properties. Nanostructure engineering provides various morphologies with the advantages of a large surface-to-volume ratio and high electron mobility compared to bulk nanoparticles. Besides, the optical properties of ZnO nanostructures are highly influenced by the size, morphology, synthesis methods/reaction conditions, types of precursors, and utilization of various surfactant materials. Das et al have reported that the use of trisodium citrate as a surfactant during the hydrothermal synthesis resulted in morphological changes . The presented ZnO morphologies produced in the presence of citrate exhibited novel photoluminescence properties and enhanced photocatalytic efficiency compared to ZnO formed without a surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Pristine, element-doped zinc oxide (ZnO), and the construction of heterojunctions with various semiconductors have made ground in many solar-related applications, such as energy conversion and storage, solar water splitting, solar cells, and photocatalytic water treatment. Especially, ZnO nanomaterials maintain their popularity due to their high optical absorption, high resistivity against photocorrosion, easy manipulation of morphology, and electrical and catalytic properties. Nanostructure engineering provides various morphologies with the advantages of a large surface-to-volume ratio and high electron mobility compared to bulk nanoparticles. Besides, the optical properties of ZnO nanostructures are highly influenced by the size, morphology, synthesis methods/reaction conditions, types of precursors, and utilization of various surfactant materials. Das et al have reported that the use of trisodium citrate as a surfactant during the hydrothermal synthesis resulted in morphological changes . The presented ZnO morphologies produced in the presence of citrate exhibited novel photoluminescence properties and enhanced photocatalytic efficiency compared to ZnO formed without a surfactant.…”
Section: Introductionmentioning
confidence: 99%